Effect of hypnobreastfeeding on the success of exclusive breastfeeding in pregnant women trimester III in Puskesmas Bungursari Tasikmalaya - Sri Wahyuni Sundari; Melsa Sagita Imaniar (Alma Ata University Press, 2021)
Background: Prevalence of stunting in Indonesia as much as 35.6%, government efforts in stunting prevention with the First 1000 Days of Life (HPK). The age of infants 0-6 months is one of the hpk period with nutritional needs is Exclusive breast milk. Mothers who have difficulties at the beginning of breastfeeding such as fatigue, feeling a little breast milk, putting milk blisters, nighttime sleep disorders, can be a source of stress of the mother, so it can interfere with the lactation process. Hypnobreastfeeding is able to bring a sense of relaxing, comfortable and calm during breastfeeding thus that the whole system in the body will run much more perfectly so that the process of breastfeeding becomes a meaningful and pleasant process for mothers and babies, Hypnobreastfeeding can meet the needs of breast milk so that the mother succeeds in lactation. Objectives: This study aims to find out how the effect of hypnobreastfeeding is done in pregnant women trimester III and seen how successful exclusive breastfeeding. Methods: This study uses quasi experiment method, sampling technique non randomised clinical trial in pregnant women trimester 3 with the number of research 30 people consists of 15 treatment groups and 15 control groups. Univariate and bivariate analysis using chi-square and multivariate statistical tests using logistic regression. Results : The results of the study obtained hypnobreastfeeding has a meaning with a value of p<0.05 ddan the effect caused by 13.00 times greater than health education with a value of OR 13.00 95% CI and coefficient determinants showed that hypnobreastfeeding predicted to affect the success of exclusive breastfeeding, Conclusions : Hypnobreastfeeding conclusion positively influenced the success of exclusive breastfeeding.